2014
DOI: 10.1039/c3tc32102a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and optical band gaps of alloyed Si–Ge type II clathrates

Abstract: Inorganic type II clathrates are low density, semiconducting allotropes of group IV elements with the potential for optoelectronic applications. This class of materials is predicted to have direct or nearlydirect band gaps, and, when Si and Ge are alloyed in the clathrate structure, the band gap is tunable in the range of 0.8-1.8 eV. In this work, we demonstrate for the first time the synthesis of alloyed Si-Ge type II clathrates. Within this alloy system, we find an amorphous region which is likely due to a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
75
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 41 publications
7
75
0
Order By: Relevance
“…Recently, Kim et al 26 reported the synthesis of a new Cmcm Si 24 allotrope free of metals, with open channels along the aaxis, formed from six and eight membered sp 3 silicon rings, and with a quasi-direct band gap of 1.3 eV. Baranowski and coauthors 24 successfully synthesized a type-II Si-Ge clathrate alloy. By changing the Ge content, they could tune the band gap in the range of 0.8-1.8 eV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Kim et al 26 reported the synthesis of a new Cmcm Si 24 allotrope free of metals, with open channels along the aaxis, formed from six and eight membered sp 3 silicon rings, and with a quasi-direct band gap of 1.3 eV. Baranowski and coauthors 24 successfully synthesized a type-II Si-Ge clathrate alloy. By changing the Ge content, they could tune the band gap in the range of 0.8-1.8 eV.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Si based clathrates have drawn attention for photovoltaic applications as a result of their tunable quasi-direct band gap in the range needed for optimal performance according to the Shockley-Queisser (SQ) limit. [21][22][23][24] Si-based clathrates without guest atoms in the cages are neutral, and thus they are intrinsic semiconductors. The guest-free low density phases are metastable at ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…22 In this work we focus on the type-II Si clathrate, which can be synthesized routinely 23 and has been investigated for PV applications. [15][16][17] The Si-Si bonds in type-II clathrates do not deviate much from the ideal sp 3 tetrahedral bonding in diamond Si. The average bond length is 2.34Å, 24 and bond angle is near 109.47 • .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] The weak interaction between guests and host facilitates tuning electronic, optical and dynamical properties of clathrates; 7 as a result, they exhibit many intriguing physical properties, such as glasslike thermal conductivity, 8 superconductivity in sp 3 covalent bonded solids 9,10 and magnetism. 11,12 Recently, Si clathrate materials have attracted intense research interest for applications including lithium ion batteries, 13 thermoelectrics, 14 photovoltaic (PV) cells and optoelectronics, [15][16][17] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Computationally, many novel well-ordered Si allotropes of various dimensionality have been proposed [9,10], but only a few of those were experimentally verified, such as the low-density Si allotropes [11] with clathrate-type structures [12][13][14][15][16][17][18][19]. The focus of the research lies on the description, understanding, and discovery of well-performing photovoltaic materials as well as models for bulk silicon surfaces [20,21].…”
Section: Introductionmentioning
confidence: 99%